Socio-economic and environmental factors affecting the rehabilitation of children with severe malnutrition - Felliyani Felliyani; Sri S Nasar; Taralan Tambunan (Indonesian Pediatric Society, 2005)
Background Poor diet and high infection rates inflicted by lowsocio-economic status and poor environments among infants andyoung children appear to be major causes of severe malnutrition.Objective To determine the practical and likely effectiveness inrehabilitation of severe malnutrition.Methods A descriptive observational study was conducted on 27children at three different sites: (1) Five inpatients at the InpatientWard, Cipto Mangunkusumo Hospital, Jakarta (IP-CM); (2) 8 out-patients at the Metabolic and Nutrition Clinic, Cipto MangunkusumoHospital (OP-CM); (3) 14 outpatients at the Nutrition Clinic, Bogor(NC). All the patients followed were aged <60 months and suf-fered from severe malnutrition (weight for length index <-3 NCHSZ-score). Subjects were followed for 12 weeks. The IP-CM groupreceived standard treatment following the WHO recommendation,while the OP-CM and NC group received proper medical treat-ment and nutrition education for mothers. The OP-CM group un-derwent more extensive laboratory investigations.Results All children generally had low socio-economic status. Mostchildren experienced poor feeding, child care, and other healthpractices. A tendency of increased prevalence, number of episodes,and duration of infectious diseases was noted in the majority ofsubjects. However, an improvement of nutritional status was ob-served during treatment in all groups, particularly in the IP-CMgroup.Conclusion Socio-economic status and environmental factorsmust be considered in the management of severe malnutrition.Educating parents concerning proper feeding and child care prac-tices appears to be of permanent nutritional benefit for the chil-dren.